# write an equation that has the sum of its roots as 3? (given that answer= x^2-3x+2)

Given Sum of roots = 3

But only from this information , we can't find equation as given (

*x*

^{2}- 3

*x*+ 2 ) .

As we know our equation , As :

*x*

^{2}- ( Sum of roots )

*x*+ ( Product of roots ) = 0

So, If we only know Sum of roots , we get

*x*

^{2}-3

*x*+ ( Product of roots ) = 0

If There is given product of roots = 2 , than we get

*x*

^{2}- 3

*x*+ 2

So,

Kindly recheck your question and get back to us , So we can help you precisely .

**
**